The Significance of Emotional Intelligence in Student Success and Its Integration into Educational Curricula - Kashif Lodhi; Dr. Atif khan; Gianfranco Rusconi; Sohail Ahmad (Corresponding Author) (Journal of Religion and Society, 2026)
This present academic paper aims to look into the vast role of emotional intelligence (EI) as a concept with relation to students’ achievement, as well as its application in the current schemes of learning. Based on the complex and composite nature of self- awareness, self-regulation, motivation, empathy and social skills, EI has come out as an influential predictor of student’s’ achievement, emotional, psychological and social growth. This review acknowledges the importance of emotional intelligence in influencing better learning atmosphere in classrooms as well as higher performance and efficient problem solving hence improving the education delivery to students. The inclusion of emotional intelligence into learning is particularly made easy by Social-Emotional Learning (SEL) programs where organizations such as the Collaborative for Academic, Social, and Emotional Learning (CASEL) has developed frameworks for its effective practice. In addition, there are tests like the Emotional Intelligence Appraisal test and the Mayer-Salovey-Caruso Emotional Intelligence Test that plays a big role in determining the EI of students and enable us to see where they stand and what they need to improve on. Nevertheless, this paper is timely in pointing out the criticism and challenges facing EI in Education such as impairment of the objectivity in assessment and training requirement for teachers and curriculum for all institutions. Ahead the concept of emotional intelligence in education gives a lot of potential for future research and practice. Firstly, further studies should focus on the standardization and confirmability of the available instruments for EI assessment. Subsequent research needs to focus on developing better and more refined instruments to assess emotional competencies of students to some extent. Second, high importance is attributed to the further assessment of the contribution of the education in EI to the students’ academic and life success. A type of research based on the investigation of student learning processes for many years can help to explain the positive impact of applying emotional intelligence to curricula. Thirdly, more ideas should be investigated on how to provide better training for teachers and how to determine what kind of curriculum modification is most suitable to infuse EI into education. Research studies could yield important gains in acquaintances with the requirements of teacher preparation and modification in their curricula to guarantee successful implementation. Finally, the use of technology for delivering the education and assessment of EI provides another potentially advantageous research direction for the future. Suppose, extending the application of digital platforms and artificial intelligence to the development of the emotional intelligence of students is considered. However, considering education as a field for the development and implementation of this concept, it is crucial to mention that the concept of emotional intelligence is still in development, and there are many opportunities for research, as well as rich possibilities to improve the effectiveness of learners’ increase and their well-being in the framework of the further advances in this field. Keywords: Role, Emotional Intelligence (EI), Students’ Achievement, Self-Awareness, Self-Regulation, Motivation